The Bizarre Bazaar: investigating gendered performance through interactive performance art - Burger, Nicolene (Centre for Film and Media Studies, 2025)
The Bizarre Bazaar: Investigating Gendered Performance through Interactive Performance Art This study investigates the persistence and evolution of structural violence as it relates to gender rooted in colonialism/apartheid within contemporary Afrikaner communities, particularly in middle and upper-class enclaves and its impact on the broader South African context. Despite South Africa's legal and political changes post-1994, many of these Afrikaner communities resist change, perpetuating nationalist forms of Afrikaner Femininity through a kind of gendered training and performance. Through critical analysis of community events (like the bazaar) as complex displays of race, class, gender, and politics, and supported by the research of Azille Coetzee, Sarah Nuttall, Christi van der Westhuizen, and Sara Ahmed, the study argues for the capacity of performance art to reveal and disrupt normative Femininity. This work seeks to create an impactful, interactive art intervention conceptualised through a circular methodology of resourcefulness and planning, and influenced by the writings of Anne Bogart, Richard Schechener, and Tim Ingold. The installation-performance piece, The Bizarre Bazaar, is the practical output of this practice-based research endeavour. Mobilising performance techniques such as juxtaposition, swarm theory, heightening the senses of the spect-actors, audience participation, and more, The Bizarre Bazaar musters the ambiguities and tensions inherent in heteronormative gendered performances - showing how bizarre these gendered expectations are and creates a bizarre performance that renders the recognisable strange. Key research questions explore how performance art can, through the investigation of traditional Feminine roles and gendered performances within community events such as bazaars, challenge and potentially transform the normalised modes of White Feminine performativity in South Africa, thus offering new identity possibilities for women.